MATERNAL METHYLMERCURY EXPOSURE THROUGH RICE INGESTION AND OFFSPRING NEURODEVELOPMENT: A PROSPECTIVE COHORT STUDY - Rothenberg, Sarah E. (Int J Hyg Environ Health, 2016)
BACKGROUND: Dietary methylmercury intake can occur not only through fish ingestion but also through rice ingestion; however, rice does not contain the same beneficial micronutrients as fish. OBJECTIVES: In rural China, where rice is a staple food, associations between prenatal methylmercury exposure (assessed using maternal hair mercury) and impacts on offspring neurodevelopment were investigated. METHODS: A total of 398 mothers were recruited at parturition at which time a sample of scalp hair was collected. Offspring (n=270, 68%) were assessed at 12 months using the Bayley Scales of Infant Development-II, yielding age-adjusted scores for the Mental Developmental Index (MDI) and Psychomotor Developmental Index (PDI). RESULTS: Among 270 mothers, 85% ingested rice daily, 41% never or rarely ingested fish/shellfish and 11% ingested fish/shellfish at least twice/weekly. Maternal hair mercury averaged 0.41 μg/g (median: 0.39 μg/g, range: 0.079–1.7 μg/g). In unadjusted models, offspring neurodevelopment (both MDI and PDI) was inversely correlated with hair mercury. Associations were strengthened after adjustment for fish/shellfish ingestion, rice ingestion, total energy intake (kcal), and maternal/offspring characteristics for both the MDI [Beta: −4.9, 95% Confidence Interval (CI): −9.7, −0.12] and the PDI (Beta: −2.7, 95% CI: −8.3, 2.9), although confidence intervals remained wide for the latter. CONCLUSIONS: For 12-month old offspring living in rural China, prenatal methylmercury exposure was associated with statistically significant decrements in offspring cognition, but not psychomotor development. Results expose potential new vulnerabilities for communities depending on rice as a staple food.